Penerapan Aplikasi Merdeka Belajar Kampus Merdeka (MBKM) Sebagai Upaya Peningkatan Kualitas Perguruan Tinggi - Aris Sudianto; Hariman Bahtiar; Muh. Farid Wajdi; Mahpuz Mahpuz (Fakultas Teknik Universitas Hamzanwadi, 2023)
Technological advances are currently developing so rapidly this has resulted in changes in social, cultural, and the world of work so that student competencies and skills must be able to adapt to the demands of the times. Therefore, Nadiem Makarim, Minister of Education, Culture, Research, and Technology of the Republic of Indonesia initiated and launched the Merdeka Learning program - Merdeka Campus as an effort to provide the best learning options for students, which is expected to be the answer to these demands. Merdeka Learning - Merdeka Campus gives students the right to take lessons outside their respective campuses but still get learning credits. The Informatics Engineering Study Program at Hamzanwadi University has currently implemented the Merdeka Learning - Merdeka Campus program. Among the 8 activities offered, there are 3 activities that are followed, namely independent studies, industrial internships, and village development. The results of the research that has been carried out show that the Merdeka Learning Information System for Merdeka Campus based on the website can help simplify the administrative process and facilitate data management